Pengaruh Pendidikan Pelatihan dan Gaya Kepemimpinan Terhadap Kinerja Anggota pada Satpas SIM Polda Metro Jaya Jakarta - Chandra Andika Yugasworo; Muhamad Arief Noor; Joned Ceilendra Saksana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Member performance as a human resource is the strength or ability of a member to produce something material or non-material, whether quantifiable or valued in money or not. With high member performance, everything the organization programs within its objectives to achieve the organization's overall goals will be quickly achieved. However, not all members have high performance; there are certainly varying levels of performance among members. Therefore, organizations must strive through established programs to improve performance to support the organization's growth, one of which is through education, training, and leadership styles. The purpose of this study was to determine the effect of education, training, and leadership styles jointly on member performance at the Jakarta Metropolitan Police's Driver's License Unit (Satpas SIM). The results of this study revealed a positive effect of education, training, and leadership styles jointly on member performance at the Jakarta Metropolitan Police's Driver's License Unit (Satpas SIM). The strength of the influence between these variables is demonstrated by the F-test of 41.512. This indicates a highly significant influence between education, training, and leadership styles on member performance at the Jakarta Metropolitan Police's Driver's License Unit (Satpas SIM).